Quality of Life for Children With Functional Abdominal Pain and Their Parents Copmared to Healthy Individuals - Hassan Karami; Bahareh Lashtoo Aghaee; Jamshid Yazdani Charati; Alame Abedi (Mazandaran University of Medical Sciences, 2022)
Objectives: Functional abdominal pain (FAP) is a debilitating disorder that has a high prevalence among children. The goal of this study is to evaluate patients' and parents' perceptions of health-related quality of life (QoL) for children with FAP. Methods: Between April 2018 and June 2019, a total of 200 children (including 100 with FAP and 100 healthy individuals) and 200 parents participated in this study. The participants completed a health-related QoL scale (pediatric quality of life inventory) that is scored on a scale from 0 (poor) to 100 (best). Children with FAP and their parents were compared to a control group consisting of healthy children. Results: Children with FAP had lower self-report QoL scores (46.97±17.43) compared to their healthy peers (78.69±13.02) and the difference was significant (P<0.05). Parents of children with FAP reported lower QoL scores compared to parents of the control group (45.56±14.19 vs 75.94±15.06, P<0.05) but it was similar to the scores for their children. Conclusions: The present study demonstrated that children with FAP and their parents experience a poor QoL compared to their healthy peers.